2015
DOI: 10.1021/acsami.5b09853
|View full text |Cite
|
Sign up to set email alerts
|

Bioglass Activated Skin Tissue Engineering Constructs for Wound Healing

Abstract: Wound healing is a complicated process, and fibroblast is a major cell type that participates in the process. Recent studies have shown that bioglass (BG) can stimulate fibroblasts to secrete a multitude of growth factors that are critical for wound healing. Therefore, we hypothesize that BG can stimulate fibroblasts to have a higher bioactivity by secreting more bioactive growth factors and proteins as compared to untreated fibroblasts, and we aim to construct a bioactive skin tissue engineering graft for wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 64 publications
1
149
0
Order By: Relevance
“…[10,36,37] However, it is unknown whether the bioactive function of these local applied biomaterials can be utilized for systemic application such as AMI treatment through intravenous injection of material derived bioactive ions. [10,36,37] However, it is unknown whether the bioactive function of these local applied biomaterials can be utilized for systemic application such as AMI treatment through intravenous injection of material derived bioactive ions.…”
Section: Discussionmentioning
confidence: 99%
“…[10,36,37] However, it is unknown whether the bioactive function of these local applied biomaterials can be utilized for systemic application such as AMI treatment through intravenous injection of material derived bioactive ions. [10,36,37] However, it is unknown whether the bioactive function of these local applied biomaterials can be utilized for systemic application such as AMI treatment through intravenous injection of material derived bioactive ions.…”
Section: Discussionmentioning
confidence: 99%
“…When the Bioglass with fibroblast cell sheets were implanted to the wound site in rat, a successful wound healing was achieved at 14 days (Figure 4(a)). 56 The wound healing and new blood vessel formation during 14 days in skin defect were higher in the Bioglass group than in the control. It was suggested that the release of ions from Bioglass significantly activated fibroblast cells to secrete proangiogenic factors such as VEGF, bFGF, and epidermal growth factor (EGF).…”
Section: Effects Of Si Ion Release On Angiogenic Events (In Vitro Andmentioning
confidence: 85%
“…These poly-thioketal urethane-based scaffolds were stable for 25 weeks in aqueous conditions but were degraded by tissue ROS in 7 weeks resulting in enhanced wound closure compared to polyester urethane dressings (Martin et al, 2014). Biomaterials based on bioglasses have recently also shown potential in enhancing wound healing and angiogenesis in animal model of wound healing (Mao et al, 2015; Xu et al, 2015; Zhao et al, 2015; Yu et al, 2016; Zhou et al, 2016). For instance, copper-doped borate bioactive glass microfibers were shown to increase both the rate of collagen deposition and angiogenesis in full-thickness wounds in rats (Zhao et al, 2015).…”
Section: Biomaterial-based Wound Therapiesmentioning
confidence: 99%